Розвиток когнітивних навичок дітей в концепції Джерома Сеймура Брунера - Мирошниченко, Олена Анатоліївна; Myroshnychenko, O. (My University, 2019)
Висвітлена проблема пізнавальних навичок школярів, відсутність когнітивних здібностей, яка обумовлена генетично. Розглянуті питання опанування дітьми предметів навчальної програми. Доведено можливості отримання позитивного результату в процесі навчання шляхом подолання труднощів викладання предметів у школі, при застосуванні методів навчання когнітивних навичок. Зроблений акцент на поняття навчання протягом життя, за вимогами сучасних професій, технологій та часу. Summary. The problem of schoolchildren’s cognitive skills, lack of cognitive abilities, which is genetically determined is highlighted. The issues of children's mastering the subjects of the core curriculum are considered. It is proved that the possibility of obtaining a positive result in the learning process by overcoming the difficulties of teaching subjects in school in the way of applying the methods of teaching cognitive skills. The concept of lifelong learning, according to the requirements of modern professions, technologies and time emphasis was placed. Some methods of developing of the studentsˈ cognitive skills and the degrees influence of these methods on the development of cognitive skills were investigated. The questions of cognitive skills development is mentioned and proved that cognitive skills as the main factor affects child development and helps to make a strong basis for further education. Life-long learning has already been an integral part for everyone’s both formation a person and a specialist in a particular sphere of life. The cognitive skills, which are formed in the childhood, have successfully developed throughout the student's training period, and in future help to get a leading specialty, to achieve high goals in life, to have an active life position. Although cognitive skills are partially congenital, most of them are acquired. If the development of cognitive skills does not occur naturally, cognitive insufficiency is formed and that reduces the potential of learning and causes difficulties to adjust without special and proper intervention. Cognitive skills can be trained and improved through proper training. Weak cognitive skills can be strengthened, and normal cognitive skills can be improved. This can be accomplished through various exercises and techniques.
The development of cognitive children's skills in the concept of Jerome Semium Bruner
Keywords: когнітивні навички; Дж. Брунер; методи навчання когнітивним навичкам; процес навчання школярів; навчання протягом життя; cognitive skills; J. Brunersˈ cognitive skills training methods; schoolchildren learning process; lifelong learning